Skill Assessment of Seasonal-to-Interannual Prediction of Sea Level Anomaly in the North Pacific Based on the SINTEX-F Climate Model - Doi, Takeshi; Nonaka, Masami; Behera, Swadhin (Frontiers in Marine Science, 2020)
Extreme sea level rise seriously impacts habitation and is indicative of changes in primary production in the North Pacific. Because of its rising trend associated with　global warming, skillful seasonal-to-interannual predictions have become increasingly valuable to guide the introduction of suitable adaptation measures that help us reduce the risks of socio-economic losses. Here, we have used a dynamical coupled ocean–atmosphere model called “SINTEX-F” to revisit the potential predictability of sea level anomalies at a lead of up to about two years. Skillful prediction is found mainly in the tropical Pacific as shown in previous work. Here, we found a new skillful prediction region in the North Pacific (30º-40ºN, 180ºW-150ºW) at about two years lead time. We also analyzed the co-variability among ensemble members and found the long-lasting ENSO/ENSO-Modoki in the tropical Pacific seems to contribute to the predictability source. The result may be useful to develop systematic and synergistic attempts to predict marine ecosystem responses to regional and global climate variations.